EFEKTIVITAS PERPUSTAKAAN DIGITAL DALAM MENUNJANG PEMBELAJARAN BAHASA INDONESIA DI SMK NEGERI 6 SURAKARTA - Alvirra, Anisyahida Aulia; Fathiha, Syalaisha Ranaisse; Arifin, David Yenu; Yunus Sulistyono (Buletin Literasi Budaya Sekolah, 2024)
The library is one of the institutions that provide information for the community and educational institutions. The existence of a digital library makes it easier for students to find information. The library has made various innovations, one of which is developing a digital library. SMK Negeri 6 Surakarta developed a digital library that aims to meet the needs of students in assisting learning activities without having to come directly to the library. The purpose of this study was to determine the effectiveness of digital libraries and factors that influence the development of digital libraries at SMK Negeri 6 Surakarta. The method used is descriptive qualitative with data collection techniques namely interviews, observation and documentation. The digital library developed by the school by spreading barcode scans in every place. Observations were also made by observing classroom learning, where researchers observed the effectiveness of digital libraries in learning.